Wpływ kapitałów zagranicznych na tworzenie warunków tzw. samopomocy w krajach rozwijających się - Gulcz, Mieczysław (Wydział Prawa i Administracji UAM, 1969)
The function of foreign capital in the development programs of underdeveloped countries is not a direct growth of standard of living but making conditions for a transition from economic stagnation to self-sustained growth. Foreign capital is indispensable to the process of take-off but the dependence on this capital should decline when economic development is progressing. It is a question whether the flow of foreign capital can create such possibility in the long run. The answer for this question necessitates an analysis from various points of view. The autor analyses only some problems of influence of foreign capital on capital accumulation in underdeveloped countries from domestic sources. Foreign capital raises the commodity production of agricultural sector and in this way it leads to growth of capital formation in this sector. The growing demand of agricultural sector, establishment of complementary investment, infrastructure, supply of know-how — all this factors stimulate the growth of capital accumulation in the private sector. Additional financial means going to the budget, directly from the foreign aid and indirectly from various taxes from foreign private capital, promote the growth of capital accumulation in the state sector.
Influence of Foreign Capital on Conditions of the So-Called Self-Help in Underdeveloped Countries